Miracle Road - March, Emily (March, Emily. Eternity Springs novel., 2013)
As their lives come together in Eternity Springs, Colorado, ex-college basketball coach Lucca Romano and schoolteacher Hope Montgomery seek to find peace from their own personal demons.